The essential Backstreet Boys [compact disc]. (Essential (Legacy Recordings), 2013)
Definitive, career-spanning and comprehensive, The Essential series features the biggest hits and best-loved songs from the most famous names in music history. Each two-CD package features classic hits and signature songs by superstar artists, plus full liner notes and photos for the complete experience. Hits include: Quit Playing Games With My Heart; I Want it That Way; Larger Than Life; Incomplete; and 26 more.